Determinan Perubahan Laba pada Perusahaan Transportasi yang Terdaftar di Indeks Saham Syariah Indonesia - muhammad abdull aziz (ITB AAS INDONESIA Surakarta, 2022)
The study tested and analyzed how the effect of financial ratios to changes in profits on transportation companies in the Indonesian Sharia Stock Index partially and simultaneously. The population as well as sampled in this study is a transportation company listed in the Indonesian Sharia Stock Index. The research period is 2016 to 2020. The results showed that simultaneously the financial ratio of CR, DER, and TATO had an influence on changes in profits. But partially the financial ratio that affects the change in profit is TATO. Cr and DER have no effect on profit changes. Based on the results of the determination test the magnitude of the Adjusted R Square value is 0.125, this means that 12.5% of the variation in profit changes can be explained by variations of three variables that affect the change in profit. The rest (100% - 12.5% = 87.5%) is explained by other variables not included in the regression equation model.